Enhancing Livelihoods of Poor Livestock Keepers through Increased Use of Fodder: Programme completion report - Duncan, Alan J.; Stür, Werner W.; Larbi, Asamoah; Tiemann, Tassilo T. (International Livestock Research Institute, 2011)
A report submitted to IFAD on the completion of the Fodder Adoption Project (FAP), (TAG 853-ILRI) programme.